2019
DOI: 10.1016/j.jneumeth.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Developing myelin specific promoters for schwannoma gene therapy

Abstract: Background: Schwannomas are peripheral nerve sheath tumors composed entirely of Schwannlineage cells that cause pain and sensory-motor dysfunction through compression of peripheral nerves, the spinal cord, and/or the brain stem. Treatment of schwannoma is largely limited to resection which itself has limited value. The goal of this study is to establish a technique to identify the most efficient and tissue-specific promoter for use in a schwannoma gene therapy construct. New Method: This work involves transfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…injection of an adeno-associated virus serotype 1 vector (AAV1) encoding proapoptotic transgenes including as caspase-1 ( ICE ) [ 12 ], N terminal fragment of gasdermin-d [ 13 ] or apoptosis-associated speck-like protein containing a CARD (caspase recruitment domain), known as ASC or PYCARD [ 14 ] in each case under control of rP0 (r = rat) cells resulted in significant reduction in tumor growth in human-derived schwannoma xenograft mouse models [ 12 ]. In these and other studies, we demonstrated that rP0 is optimal for both tissue specificity, and critically, protecting neuronal tissue from potential off-target toxicity [ 12 , 14 , 15 , 16 ].…”
Section: Introductionsupporting
confidence: 59%
“…injection of an adeno-associated virus serotype 1 vector (AAV1) encoding proapoptotic transgenes including as caspase-1 ( ICE ) [ 12 ], N terminal fragment of gasdermin-d [ 13 ] or apoptosis-associated speck-like protein containing a CARD (caspase recruitment domain), known as ASC or PYCARD [ 14 ] in each case under control of rP0 (r = rat) cells resulted in significant reduction in tumor growth in human-derived schwannoma xenograft mouse models [ 12 ]. In these and other studies, we demonstrated that rP0 is optimal for both tissue specificity, and critically, protecting neuronal tissue from potential off-target toxicity [ 12 , 14 , 15 , 16 ].…”
Section: Introductionsupporting
confidence: 59%
“… 30 , 31 Recent studies also support regression of schwannomas using proteins that induce cell death under a Schwann cell-specific promoter. 32 , 33 , 34 The current study demonstrates that AAV-based delivery of functional merlin produces inhibition of mTORC1 activation in human NF2 -null ACs and SCs in culture. Further, we describe a new sciatic nerve xenograft model in nude mice for schwannomas using human NF2 -null immortalized SCs for which a single intratumoral injection of the AAV-merlin vector leads to regression of tumors.…”
Section: Introductionmentioning
confidence: 61%
“…Still, more detailed biodistribution and toxicity studies would be required in follow-up preclinical toxicology studies before consideration of clinical trials. If toxicity to other cell types is found, merlin could be expressed under a SC-specific promoter, such as for P0 30 , 34 or periostin. 39 …”
Section: Discussionmentioning
confidence: 99%